Upaya Keselamatan Kerja Bagi Bidan dalam Pertolongan Persalinan dengan Alat Perlindungan Diri (Safety Measures For The Midwife In Aid Delivery By Means Of Personal Protection) - Tri Suwarni; Chusnul Chotimah (Indonesian Journal on Medical Science, 2015)
Abstract: The midwife is someone who has followed the midwife education program that is recognized in the country, has graduated from the education and qualified to be registered or have a valid license to practice midwifery and can be placed on the unit - the government health units. One form of the main services provided by midwives is Normal Delivery Care (APN). APN implementation can not be separated from the use of medical devices that potentially disease transmission. Given the high risk of health problems in hospitals, especially midwives, there should be efforts to prevent the occurrence of diseases caused by the working environment. One of them is the use of personal protective equipment (Suma'mur, 1981). Type of qualitative observational research with cross sectional approach. The data used is the result of in-depth interviews to key informants and triangulation. Key informants midwives in hospitals VK space Sukoharjo, informant triangulation among others Chief Medical Officer of the district. Sukoharjo, Director of Hospital District. Sukoharjo and Chairman of the Kab IBI Sukoharjo. The use of PPE in deliveries in the district hospitals. Sukoharjo influenced by factors that are synergistic communication, resources, disposition / attitude executor (midwife) and a bureaucratic structure. The success of the program the use of personal protective equipment can be achieved by involving all parties concerned.Keywords: Analysis, Delivery Assistance, Personal Protection Equipment Abstrak: Bidan adalah seseorang yang telah mengikuti program pendidikan bidan yang diakui di negaranya, telah lulus dari pendidikan tersebut serta memenuhi kualifikasi untuk didaftar dan atau memiliki izin yang sah untuk melakukan praktik bidan dan dapat ditempatkan pada unit – unit kerja pemerintah bidang kesehatan. Salah satu bentuk pelayanan utama yang diberikan oleh bidan adalah Asuhan Persalinan Normal (APN). pelaksanaan APN juga tidak terlepas dari penggunaan alat kesehatan yang berpotensi terjadi penularan penyakit. Melihat tingginya resiko terhadap gangguan kesehatan di Rumah Sakit khususnya bidan, maka perlu dilakukan upaya pencegahan terhadap kejadian penyakit akibat lingkungan kerja. Salah satu diantaranya adalah penggunaan alat perlindungan diri (Suma’mur, 1981). Jenis penelitian ini observasional kualitatif dengan pendekatan cross sectional. Data yang digunakan merupakan hasil wawancara mendalam kepada informan utama dan triangulasi. Informan utama yaitu bidan di ruang VK RSUD Sukoharjo, informan triangulasi antara lain Kepala Dinas Kesehatan Kab. Sukoharjo, Direktur RSUD Kab. Sukoharjo dan Ketua IBI Kab Sukoharjo. Penggunaan APD pada pertolongan persalinan di RSUD Kab. Sukoharjo dipengaruhi oleh faktor yang sinergis yaitu komunikasi, sumber daya, disposisi / sikap pelaksana (bidan) dan struktur birokrasi. Keberhasilan program penggunaan alat perlindungan diri dapat dicapai dengan melibatkan seluruh pihak yang terkait.Kunci : Analisis, Pertolongan Persalinan, Alat Perlindungan Diri